Performance of Indian gooseberry (Emblica officinalis) cultivars under arid region of India - Shukla, Arun K; Singh, D; Shukla, Anil K (The Indian Journal of Agricultural Sciences, 2011)
An experiment was conducted during 2001–05 to evaluate the performance of different cultivars of gooseberryEmblica officinalis Gaertn, viz ‘Krishna’ ‘Kanchan’ ‘Chakaiya’ ‘NA 6’ ‘NA 7’ ‘NA 10’ ‘Anand 1’ and ‘Anand 2’ underarid ecosystem. Observations on growth parameters, time of fruit set and maturity, fruit drop, yield-attributing traits,quality parameters were recorded. The plant height was varied from 2.10 to 3.45 m. Canopy spread in east-west andnorth-south directions varied from 2.75 m to 4.0 m and 3.0 m to 4.20 m respectively. Fruit length was maximum in‘Krishna’ (4.30 cm), followed by ‘NA 6’ (3.85 cm) and ‘Chakaiya’ (3.73 cm) minimum was found in ‘Anand 2’ (2.97cm). Fruit set was recorded maximum in ‘NA 7’ (49.2%) with minimum in ‘Anand 1’ (25.9%) and fruit retention wasvaried from 6.00 to 11.4% with maximum in ‘NA 7’ (11.4%) and minimum in ‘Anand 2’ (6.00%). The maximum fruitbreadth was observed in ‘Krishna’ (4.26 cm) and minimum in ‘Anand 2’ (3.00 cm). Fruit weight was maximum in‘Krishna’ (49.3 g) and minimum in ‘Anand 2’ (28.66 g). The fruit yield/tree was recorded maximum in ‘NA 7’ (105 kg)and minimum in ‘Anand 1’ (25.3 kg). VitaminC was varied from 433.9 to 678.2 mg/100 g fruit pulp and TSS variedfrom 14.9 to 19.3%.